Case Report: COVID-19 exacerbates acute lower limb ischemia in patients with popliteal artery entrapment syndrome - Bo, Li; Xiaojiong, Du (Frontiers in Cardiovascular Medicine, 2024)
Non-traumatic lower limb ischemic diseases are extremely rare among young people. Clinically, they are mainly seen in the form of popliteal artery entrapment syndrome (PAES). In addition, with the prevalence of COVID-19 infection, more and more studies report that COVID-19 infection may lead to arteriovenous thrombosis, which could cause lower limb ischemia. This case reported that a 31-year-old male amateur football player who developed intermittent claudication after recovering from COVID-19. After 2 months of consultation, he was ultimately diagnosed with PAES. As is well known, PAES is mostly caused by long-term compression of the popliteal artery by abnormal anatomical structures, resulting in thickening of the vascular outer membrane and progression of the disease until intimal damage and thrombosis, leading to lower limb ischemia. During the progression of the disease, there may be multiple factors that accelerate its progression. Therefore, combined with the patient's clinical history and related studies on confirmed thrombosis caused by COVID-19, we can infer that COVID-19 could accelerate the occurrence of PAES.